Ethnic Identification, Intermarriage, and Unmaresured Progress by Mexican Americans - Brian Duncan; Stephen Trejo (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
Using Census and CPS data, we show that U.S.-born Mexican Americans who marry non- Mexicans are substantially more educated and English proficient, on average, than are Mexican Americans who marry co-ethnics (whether they be Mexican Americans or Mexican immigrants). In addition, the non-Mexican spouses of intermarried Mexican Americans possess relatively high levels of schooling and English proficiency, compared to the spouses of endogamously married Mexican Americans. The human capital selectivity of Mexican intermarriage generates corresponding differences in the employment and earnings of Mexican Americans and their spouses. Moreover, the children of intermarried Mexican Americans are much less likely to be identified as Mexican than are the children of endogamous Mexican marriages. These forces combine to produce strong negative correlations between the education, English proficiency, employment, and earnings of Mexican-American parents and the chances that their children retain a Mexican ethnicity. Such findings raise the possibility that selective ethnic "attrition" might bias observed measures of intergenerational progress for Mexican Americans.
Keywords: 330; Migration